Single-staged transoral intra-lesional excision of aneurysmal bone cyst of axis (C2) vertebra and temporary stabilization of upper cervical spine in an adolescent: A case report - Mor Japar Khan, Ed Simor Khan; Ab Wahid, Hazwan; Sharifudin, Mohd Ariff; Ramos, J; Pingel, Andreas; Kandziora, Frank M. (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
Aneurysmal bone cyst (ABC) infrequently occurs within the upper cervical vertebrae. Various therapeutic options have been reported in the literature. We would like to share our experience in managing a case of a 16-year-old girl diagnosed with ABC at the body of axis (C2) vertebra. Serious attention had to be given on the stability of the cervical spine following tumour resection, which can be affected by the mode of treatment chosen. Instability can have a detrimental effect on the cervical spine, in which case may necessitate further surgery. We performed a single-staged intra-lesional curettage via a transoral approach and temporary non-fusion posterior stabilization of C1 lateral mass screw and C2 pedicle screw. The implants were removed after six months once ossification of C2 has taken place to regain full motion of the neck. There was no evidence of recurrence or instability of the cervical spine three years following surgery.